A Young Lady with Headache and Abnormal Behavior - Mahbub, MD Shahriar; Imran Khan, Mohammad Ashik; Siddiqui, MMR; Ahasan, HAM Nazmul (Journal of Medicine, 2011)
DOI: http://dx.doi.org/10.3329/jom.v12i2.8430 JOM 2011; 12(2): 192